Algae-functionalized hydrogel-gated organic field-effect transistor. Application to the detection of herbicides. (10th March 2021) - Gall, Jérémy Le; Vasilijević, Sandra; Battaglini, Nicolas; Mattana, Giorgio; Noël, Vincent; Brayner, Roberta; Piro, Benoît
Highlights: A hydrogel-gated organic field-effect transistor for pollutants monitoring. Entrapment of cyanobacteria in an alginate hydrogel grafted on a platinum electrode. Amplification of a gate redox current into a source-drain current. Monitoring the photosynthetic activity of cyanobacteria with a transistor. Abstract: In this work, a first demonstration of an hydrogel-gated organic field-effect transistor (HGOFET) for the detection of water pollutants is described. Photosynthetic cyanobacteria were entrapped in a hydrogel grafted onto the platinum gate of the transistor. Photosynthesis was continuously monitored by electroreduction of the oxygen produced or consumed by the cyanobacteria on the gate electrode, under illumination or in the dark, respectively. The presence of herbicides such as diuron and glyphosate was found to strongly affect the cyanobacteria's photosynthetic activity, which was transduced into a significant drop of the device's gate current, strongly amplified onto the drain. This study demonstrates the suitability of HGOFETs for environmental monitoring. Graphical abstract: Image, graphical abstract